Producción y exportación de concentrado de maracuya ecuatoriano en el cantón Arenillas provincia El Oro para exportación a Alemania - Romero Chavez, Vicente Xavier (2018)
Ecuador's global participation in the production and marketing of passion fruit occurred in the 1960s, after Colombia, despite the fall in international prices, the fruit continued to be produced and processed in significant volumes, so it was possible to export to the United States of America, Europe, Chile, Argentina and Brazil, a demand that has allowed the development of better agricultural techniques. The general objective of the titration work was "To elaborate a feasibility project for the production and commercialization to Germany of passion fruit concentrate to promote the productive development and the diversification of the exportable supply; The specific objectives were: 1. Analyze the market of German fruit juices and concentrates to know the supply demand of the product and determine the feasibility of export; 2. Establish the technical requirements, production costs, administration and sales, investment and income required for the start-up of the production plant; 3. Carry out a financial study to determine the feasibility of the project, which includes the net present value (NPV), internal rate of return (IRR), recovery period, cost benefit ratio, break-even point. Within the market study analyzed the statistics of passion fruit production in Ecuador, as well as its export to Germany, results that were projected to obtain the respective unsatisfied demand, which was 612,371,010 kilos per year 2021 , while the apparent consumption was 45049.06 metric tons, in addition to this, apparent national demand and per capita consumption were also calculated. The projection of the demand of Germany determined the existence of 49246,92 metric tons per year 2021. The per capita consumption calculated was 0.55 kg per person. In accordance with the proposed investment plan, the fixed assets amount to US $ 715,766.90, which will be financed by 95.04%. Regarding investment in land and buildings, the company will require $ 54,155.00. The values corresponding to the production plant amount to $ 29,155.00, while the machinery and equipment involved in the process add up to $ 53376. The respective technical and financial analysis was made, the results were positive in this regard , the Net Present Value (NPV) was $ 705,758.16 and the internal rate of return of 25%. The unit production cost of the passion fruit pulp kg was $ 1.99, through which the price of the product was obtained taking into account the profit margin of 26%, establishing the retail price of $ 2.50. The estimate of exports for the first year was 17 containers, this is equivalent to 419.461 kg of concentrate, with a growth of concentrate production to export 20 containers, generating sales revenue during the first year of $ 1,047,872 dollars and $ 1,524,763 for the fifth year of production. To reach an adequate balance point, the company must sell during the first year $ 703,035 to cover its costs and expenses and $ 774,110 for the fifth year. The investment in question would be recoverable in a period of approximately three years. The project in question is feasible to perform because there is a favorable unmet demand.